Comparison between next‐generation and Sanger‐based sequencing for the detection of transmitted drug‐resistance mutations among recently infected HIV‐1 patients in Israel, 2000–2014. Issue 1 (11th August 2017) - Moscona, Roy; Ram, Daniela; Wax, Marina; Bucris, Efrat; Levy, Itzchak; Mendelson, Ella; Mor, Orna
Abstract: Introduction : Transmitted drug‐resistance mutations (TDRM) may hamper successful anti‐HIV‐1 therapy and impact future control of the HIV‐1 epidemic. Recently infected, therapy‐naïve individuals are best suited for surveillance of such TDRM. In this study, TDRM, detected by next‐generation sequencing (NGS) were compared to those identified by Sanger‐based population sequencing (SBS) in recently infected HIV‐1 patients. Methods : Historical samples from 80 recently infected HIV‐1 patients, diagnosed between 2000 and 2014, were analysed by MiSeq (NGS) and ABI (SBS). DeepChek‐HIV (ABL) was used for interpretation of the results. Results : Most patients were males (80%); Men who have sex with men (MSM) was the major transmission group (58.8%). Overall, TDRM were detected in 31.3% of patients by NGS and 8.8% by SBS, with SBS TDRM restricted to persons infected with subtype B. All SBS‐detected TDRM were identified by NGS. The prevalence of TDRM impacting protease inhibitors (PI), nucleoside reverse transcriptase inhibitors (NRTI) and non‐nucleoside reverse transcriptase inhibitors (NNRTI) was 11.3, 26.2 7.5%, respectively, in NGS analyses and 0, 3.8 and 5%, respectively, in SBS analyses. More patients with NGS and SBS TDRM were identified in 2008–2014 (37.2% or 13.9%, respectively) compared to 2000–2007 (24.3% or 2.7%, respectively), and a significantly greater number of these patients had multiple NGS TDRM. The most abundant, albeit, minor‐frequency RT TDRM, were the K65R and D67N, while K103N, M184V and T215S were high‐frequency mutations. Minor TDRM did not become a major variant in later samples and did not hinder successful treatment. Conclusions : NGS can replace SBS for mutation detection and allows for the detection of low‐frequency TDRM not identified by SBS. Although rates of TDRM in Israel continued to increase from 2000 to 2014, minor TDRM did not become major species. The need for ongoing surveillance of low‐frequency TDRM should be revisited in a larger study.